2022
DOI: 10.54099/aijb.v1i1.65
|View full text |Cite
|
Sign up to set email alerts
|

Tax Planning on The Multinational Companies in Indonesia

Abstract: The discussion of this review is motivated by the problems of multinational companies, especially in Australia, America and Indonesia, which prefer tax planning efforts with Tax avoidance. The purpose of this paper is knowledge of tax planning in multinational companies that occur as a result of business transactions. The results of the discussion prove that each country carries out tax avoidance using 2 (two) measurements, namely the Effective Tax Rate (ETR) and Book Tax Differences (BTD). This writing descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
2
Order By: Relevance
“…Menurut Novita, W., & Fahmy, R. (2022) untuk melihat bagaimana besar dampak adanya pengaruh dari pajak terhadap pendapatan maka perlu untuk melihat seberapa besar kontribusi dari sector pajak tersebut dalam pendapatan secara total. Selanjutnya Sari, dkk (2022) Pendapatan Asli Daerah (PAD) adalah pendapatan yang diperoleh daerah yang dipungut berdasarkan peraturan daerah sesuai dengan peraturan perundang-undangan.…”
Section: Pendahuluanunclassified
“…Menurut Novita, W., & Fahmy, R. (2022) untuk melihat bagaimana besar dampak adanya pengaruh dari pajak terhadap pendapatan maka perlu untuk melihat seberapa besar kontribusi dari sector pajak tersebut dalam pendapatan secara total. Selanjutnya Sari, dkk (2022) Pendapatan Asli Daerah (PAD) adalah pendapatan yang diperoleh daerah yang dipungut berdasarkan peraturan daerah sesuai dengan peraturan perundang-undangan.…”
Section: Pendahuluanunclassified
“…Research related to the study of Indonesian tax incentive literature is still very limited, especially in Indonesia, among the relevant studies, namely Irwanto & Meilani (2022) explaining a comparison of tax incentives in Indonesia, Malaysia and the United States. Other relevant research includes Dwianika et al (2021) explaining a review of tax compliance in Indonesia during the COVID-19 Pandemic; Safitri & Widarjo (2023) explain research developments related to tax evasion; Ibrahim et al (2018) explain tax policy in Indonesia in the energy sector; Sari et al (2023) reviewed tax compliance research mapping in Indonesia; and Novita & Fahmy (2022) explain tax planning in multinational companies that occur as a result of business transactions in Indonesia. More recent tax incentive studies can be found in research by Ali et al, (2022), Dai & Chapman (2022), Todorovic et al, (2022), and Song et al, (2020.…”
Section: Previous Studymentioning
confidence: 99%
“…Dalam prinsip akuntansi di Indonesia, besar beban imbalan kerja yang akan mengurangi cadangan imbalan kerja dalam neraca adalah sebesar perhitungan aktuaria. Sedangkan dalam prinsip pajak, besar beban yang harus dikurangkan adalah sebesar yang dibayarkan kepada karyawan atau menganut cash basis (Husnaini, et al, 2017;Manzon & Plesko, 2002;Novita & Rahmi Fahmy, 2022;Ramadhani, et al, 2017). Kedua, penelitian ini menambahkan variabel kepemilikan keluarga pada model persistensi laba yang diajukan oleh Tang & Firth (2012).…”
Section: Pendahuluanunclassified